Studi Pemetaan Sistematis Mengenai Internasionalisasi pada Sektor Pertanian - Deliani Azmi Zakiah Ahmad; Muhamad Rizal; Pratami Wulan Tresna (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study presents a Systematic Mapping Study on the topic of internationalization, with a particular contextual focus on the agricultural sector. Internationalization in this context extends beyond sports to encompass research collaborations, strategic alliances, and the adoption of cross-border technologies. Although the agricultural sector holds a significant role in the global economy, scholarly attention to its internationalization processes remains relatively limited compared to other sectors. This mapping study identifies research trends, methodological approaches, and key thematic areas across existing literature. The findings reveal stagnation in publication activity, with notable growth only emerging in 2024. Most studies apply survey-based methods and primarily investigate the drivers of internationalization. Future research is needed to broaden geographical representation, diversify methodological perspectives, and address gaps in the current body of knowledge.